Implementasi Kurikulum Merdeka Dalam Pembelajaran IPAS di SD 1 Tanjungrejo - Winarni, Arum; Ismaya, Erik Aditia (Jurnal Ilmiah Wahana Pendidikan, 2024)
The aim of this research is to analyze the implementation of the independent curriculum in elementary schools. This research uses a descriptive qualitative approach, data collection techniques using observation, interviews and documentation, data analysis includes data reduction, data presentation, concluding drawing. The results of this research are that in independent learning curriculum teachers have implemented independent learning. Where teachers are given the freedom to implement meaningful, differentiated and innovate learning. Teachers and students have also used appropriate approaches, models, strategies and learning methods. Learning design has taken into account aspects of simplicity, harmony, easy to understand, flexibility and taking into account the characteristics of students. The application of the independent curriculum using independent changes provides flexibility to educational units when implementing the independent curriculum using the teaching tools that have been provided. The obstacles encountered are teachers' limitations in creating teaching modules, compiling learning plans due to adaptation of the new curriculum, minimal socialization and training and limited school infrastructure.